Representasi Nilai Filsafat Stoikisme Tokoh Utama Novel Tentang Kamu Karya Tere Liye - Firliyana, Nur; Fitrah, Yundi; Rahariyoso, Dwi (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
This study aims to analyze the representation of Stoicism philosophical value ​in the main character in the novel Tentang Kamu by Tere Liye. The value is in the form of a dichotomy of control. This study uses a descriptive qualitative approach with data collection using reading and note-taking techniques on the research object of the novel Tentang Kamu by Tere Liye. The data is in the form of the main character's character that represents the dichotomy of control of Stoicism philosophical values ​​which are analyzed using the nature of characterization by Burhan Nurgiyantoro. The results of the study showed twelve data on the dichotomy of control values ​​consisting of descriptions through narration 2 data, descriptions through the main character's dialogue 1 data, descriptions through interactions between other characters 3 data, descriptions through the thoughts of other characters towards the main character 2 data. Based on the results of the study, it can be concluded that the main character in the novel Tentang Kamu represents the value ​of Stoicism philosophy. Proven by the findings in the form of dichotomy of control value ​​fulfilling all elements of the nature of characterization so that the representation of dichotomy of control values ​​through the main character is easily understood by the reader. Abstrak Penelitian ini bertujuan untuk menganalisis repsentasi nilai filsafat Stokisme tokoh utama novel Tentang Kamu karya Tere Liye. Nilai tersebut berupa dikotomi kendali. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data penelitian teknik baca dan catat pada objek penelitian novel Tentang Kamu karya Tere Liye. Data berupa karakter tokoh utama yang merepresentasikan dikotomi kendali nilai filsafat Stoikisme dianalisis menggunakan hakikat penokohan oleh Burhan Nurgiyantoro. Hasil penelitian menunjukkan nilai dikotomi kendali terdiri atas deskripsi melalui narasi 2 data, deskripsi melalui dialog tokoh utama 1 data, deskripsi melalui interaksi antar tokoh lain 3 data, deskripsi melalui pikiran tokoh lain terhadap tokoh utama 2 data. Berdasarkan hasil penelitian disimpulkan tokoh utama novel Tentang Kamu merepresentasikan nilai filsafat Stoikisme, dibuktikan dengan nilai dikotomi kendali memenuhi semua unsur hakikat penokohan sehingga representasi nilai dikotomi kendali tokoh utama dipahami dengan mudah oleh pembaca.